2014
DOI: 10.1021/jm401144z
|View full text |Cite
|
Sign up to set email alerts
|

Drug Design Targeting Protein–Protein Interactions (PPIs) Using Multiple Ligand Simultaneous Docking (MLSD) and Drug Repositioning: Discovery of Raloxifene and Bazedoxifene as Novel Inhibitors of IL-6/GP130 Interface

Abstract: The IL-6/GP130/STAT3 pathway is critical for the progression of multiple types of cancers. We report here the discovery of raloxifene and bazedoxifene as novel inhibitors of IL-6/GP130 protein-protein interactions (PPIs) using multiple ligand simultaneous docking (MLSD) and drug repositioning approaches. Multiple drug scaffolds were simultaneously docked into hot spots of GP130 D1 domain by MLSD to compete with the key interacting residues of IL-6, followed by tethering to generate virtual hit compounds. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 35 publications
4
123
0
1
Order By: Relevance
“…A number of BCL-2/BH3 PPI inhibitors such as GX15-070 and AT-101 are used in early clinical trials for a variety of solid tumors, including lung carcinoma and GIST, with more expectation (150, 151). Utilizing a multiple ligand simultaneous docking (MLSD) model, a group has identified raloxifene and bazedoxifene as potent inhibitors of the IL-6/GP130 interface, a critical step in the STAT3-mediated pathway of cancer progression (152). In the context of cerebral ischemia and neuropathic pain, GABAB receptors are often excessively upregulated (153, 154), and small peptides interfering with GABA-interacting proteins such as 14–3–3 may selectively restore normal GABA function without affecting the GABA receptors not implicated in disease (155, 156).…”
Section: Ais Targeting As a Pharmacological Strategymentioning
confidence: 99%
“…A number of BCL-2/BH3 PPI inhibitors such as GX15-070 and AT-101 are used in early clinical trials for a variety of solid tumors, including lung carcinoma and GIST, with more expectation (150, 151). Utilizing a multiple ligand simultaneous docking (MLSD) model, a group has identified raloxifene and bazedoxifene as potent inhibitors of the IL-6/GP130 interface, a critical step in the STAT3-mediated pathway of cancer progression (152). In the context of cerebral ischemia and neuropathic pain, GABAB receptors are often excessively upregulated (153, 154), and small peptides interfering with GABA-interacting proteins such as 14–3–3 may selectively restore normal GABA function without affecting the GABA receptors not implicated in disease (155, 156).…”
Section: Ais Targeting As a Pharmacological Strategymentioning
confidence: 99%
“…21,22,66 Homodimerization of the IL-6/IL-6Ra/gp130 heterotrimers triggers phosphorylation of the gp130-associated Janus kinase, and subsequent phosphorylation of tyrosine residues on the intracellular cytoplasmic tail of gp130 generates docking sites for the SH2 domains of STAT3. 21,22,24,66 JAK-mediated phosphorylation of the tyrosine-705 residue of STAT3 recruited to the activated IL-6/IL-6Ra/gp130/JAK complex enables reciprocal interactions between SH2 domains of pSTAT3 monomers to form dimers, which then translocate into the nucleus. 4,21,22,24,66 In the nucleus, pSTAT3 dimers bind to specific DNA response elements in the promoters that activate the transcription of target genes that favor the development, progression, and maintenance of HNSCC and many other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,24,66 JAK-mediated phosphorylation of the tyrosine-705 residue of STAT3 recruited to the activated IL-6/IL-6Ra/gp130/JAK complex enables reciprocal interactions between SH2 domains of pSTAT3 monomers to form dimers, which then translocate into the nucleus. 4,21,22,24,66 In the nucleus, pSTAT3 dimers bind to specific DNA response elements in the promoters that activate the transcription of target genes that favor the development, progression, and maintenance of HNSCC and many other tumors. [1][2][3][4]7 However, IL-6 can also activate signaling in tissues and cells that do not express the IL-6Ra receptor by a trans-signaling process.…”
Section: Discussionmentioning
confidence: 99%
“…The program, as its name indicates, docks two compounds simultaneously using a scoring function that evaluates docking of each molecule on the target protein with the AutoDock4 scoring function [85] and interaction between the compounds. MLSD was applied to design a SMPPII for the IL-6/GP130 interface [86]. Before running MLSD, the authors identified hotspot residues by molecular dynamics simulation, and defined a docking box that covers the hotspots.…”
Section: Computational Methods 2: Hot Spots and Fragment-based Metmentioning
confidence: 99%
“…MLSD identified potent fragment combinations, and the combinations were further grown to full ligands, which were found to be similar to two existing drugs (drug repositioning). The identified drugs from repositioning were validated as SMPPIIs by experiment [86]. …”
Section: Computational Methods 2: Hot Spots and Fragment-based Metmentioning
confidence: 99%